2024
DOI: 10.3390/met14030331
|View full text |Cite
|
Sign up to set email alerts
|

Elimination of Low-Angle Grain Boundary Networks in FeCrAl Alloys with the Electron Wind Force at a Low Temperature

Md Hafijur Rahman,
Sarah Todaro,
Luke Warner
et al.

Abstract: Low-angle grain boundaries (LAGBs) accommodate residual stress through the rearrangement and accumulation of dislocations during cold rolling. This study presents an electron wind force-based annealing approach to recover cold-rolling induced residual stress in FeCrAl alloy below 100 °C in 1 min. This is significantly lower than conventional thermal annealing, which typically requires temperatures around 750 °C for about 1.5 h. A key feature of our approach is the athermal electron wind force effect, which pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…35) In our previous study, we have also demonstrated the efficacy of EWF assisted low-temperature processing in defect mitigation of metals and alloys. 36) Here, we extend our investigation to intentionally degraded devices, assessing EWF's effectiveness in defect mitigation within semiconductor devices, thus providing a comprehensive strategy for ensuring the longevity and reliability of these components in practical scenarios.…”
mentioning
confidence: 99%
“…35) In our previous study, we have also demonstrated the efficacy of EWF assisted low-temperature processing in defect mitigation of metals and alloys. 36) Here, we extend our investigation to intentionally degraded devices, assessing EWF's effectiveness in defect mitigation within semiconductor devices, thus providing a comprehensive strategy for ensuring the longevity and reliability of these components in practical scenarios.…”
mentioning
confidence: 99%